Library Service Innovations to Attract Millennials - Fajar Saripudin; Pajar Syadid Munawar; Risa Karundeng; Sabiila Nurjannah; Irpan Taupik Hidayat (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
In the digital era like today, convenience can be found and obtained by anyone and anywhere. Library digitization needs to be done because in addition to keeping up with technological advances, digitalizing libraries can also maintain existence among the millennial generation. As a millennial generation who can get anything they need without having to wait long, of course, getting the desired information doesn't take long either. During the development and advancement of technology, the ease and freedom to get information are very open, not limited by anything except for several rules that regulate the distribution of information. To obtain supporting data, a literature study method is used. The results of this paper provide answers related to digitalization efforts as an effort to maintain the existence of the library. The answers produced are recommended for parties who need related information, especially for libraries that are still in the digitalization development period. The increasingly developing era of digitalization is very necessary to continue to innovate in library services to attract the interest of millennial users.